Copolymers of (2-cyclohexylidene-1,3-dioxolane-4-yl) methyl methacrylate with acrylonitrile and styrene: Synthesis, characterization, and monomer reactivity ratios - Ilter, Z; Coskun, M; Erol, I (Wiley, 2001)
The copolymerization of (2-cyclohexylidene-1,3-dioxolane-4-yl) methyl methacrylate monomer with styrene and acrylonitrile were carried out in 1,4-dioxane solution at 60 degreesC using BPO as an initiator. The copolymers were characterized by Fourier transform infrared, H-1 NMR, and C-13 NMR spectroscopic techniques. Thermal properties of the polymers were also studied by thermogravimetric analysis and differential scanning calorimetry. The copolymer compositions were determined by elemental analysis. The monomer-reactivity ratios were calculated by the application of conventional linearization methods as a result of Fineman-Ross and Kelen-Tudos to less than 1 for both monomers. (C) 2001 John Wiley & Sons, Inc.
Keywords: 2-cyclohexylidene-1,3-dioxolane-4-yl-methyl methacrylate; copolymers; characterization; monomer; reactivity ratios; elemental analysis